Formet Rebellion Movement In Power:A Challenge Of Perfornance Prllfng - Suwandono & Grace Lestariana Wonoadi (FISIP UMY, 2015)
Some nalion-stales are slill lacing rebellion movements that saying lhey walked in ihe ditlerent path ol hislory ol the slate and/or disappoinled lo lhe regime's perlormance. For this reason, am conflict, separalism, and other ellort to lorm a new regime happened. Giving a specilic autonomy to the rebellion movemenl to govern rn a specilic region is a common alternalive to reduce lhe wolse impacl. lt is a kind oi recognition that they know well their needs. Sending lhe fomer rebellion movemenl to power is an attempl to aggregate therr inleresls that nol accommodaled lor a long trme lt is hope that it will reduce the lension between lhe cenlral govemment and lhe movemenl as well as the spread of violence to be a regional or inlemational $sue ln some cases, however, il did not work, even counler-productive. The new regime's performance changed from a solid, tast movinq and Iesponsive opponent to be a corrupl and full ol intrigues administration This paper aims to study management panern of governance led by lhe former rebellion movement aclivisls ll is an anempl to do theory building in conllicl managemenl. Comparing [4NLF in lhe Philrpprnes, HAI4AS in Palesline, and GAM in lndonesia will be uselul lo ful{ill lhe need.